KREATIVITAS GURU BAHASA ARAB DALAM PENGGUNAAN MEDIA PEMBELAJARAN DI MADRASAH TSANAWIYAH NEGERI (MTsN) 2 MEDAN - Samsul Haq; Dini Febria Arifina; Nur Zakiah Harahap; L'Niana Aulia Zuhri (Yayasan Haiah Nusratul Islam, 2023)
Learning is an interaction process that occurs between two parties whi need each other, namely the teacher and students and is connected by a third party, namely material or teching materials. The teacher is considerd a facilitator in the learning process an must be able to create a pleasant learning atmosphere so that studentas are not seen as watching. Teachers are required to always be innovative and creative, one of which is by using learning media with a variety of creativity. Learning media is not only used in several special subjects but can also be used in the field of languange. This research was conducted to find out how creativ arabic theacer in MTsN. 2 Medan are in using a qualitative research methode system of descriptive anlysis which is then reinforced by several expert theoris, so the results of the discussion that need ti be obtained are that Arabic languange teachers in MTsN. 2 Medan are quites creative in using learning media. This is because when using Arabic languange learning media there are at least four things that teachers must pay attention.